SOME PROPERTIES OF MATROIDS OBTAINED FROM CONCEPT LATTICE APPROACHES - hua mao (IndoMS, 2016)
Using the Hasse diagrams of concept lattices, we investigate therelations between matroids and geometric contexts, followed byjudging a mathematical construction to be a matroid. We provide anidea to find out the dual of a matroid from the ways of conceptlattice drawing. In addition, we utilize the Hasse diagrams ofconcept lattices to discuss the minors of matroids, direct sum ofmatroids and the connectivity of a matroid. All the consequences demonstrate that the theory of concept lattice drawing can be usedinto matroids. This generalizes the applied fields of conceptlattices.DOI : http://dx.doi.org/10.22342/jims.22.2.267.183-190